2006
DOI: 10.1093/ije/dyl056
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of empirical research on self-reported racism and health

Abstract: This paper reviews 138 empirical quantitative population-based studies of self-reported racism and health. These studies show an association between self-reported racism and ill health for oppressed racial groups after adjustment for a range of confounders. The strongest and most consistent findings are for negative mental health outcomes and health-related behaviours, with weaker associations existing for positive mental health outcomes, self-assessed health status, and physical health outcomes. Most studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

89
1,161
4
43

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,383 publications
(1,315 citation statements)
references
References 149 publications
89
1,161
4
43
Order By: Relevance
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
“…Numerous review articles have found that racial/ethnic discrimination contributes to variations in health risks within racial and ethnic minorities (Brondolo, Gallo, & Myers, 2009b;Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Racial/ethnic Discrimination and Psychological Well-beingmentioning
confidence: 99%
“…4 Moreover, to the extent that deficits in community resources are perceived as the result of racism, residents again are at risk of negative health outcomes. 31,32 Longitudinal research is also needed to investigate whether retail redlining perpetuates disadvantage. As noted earlier, measures of retail demand may derive in part from reported behaviors, rather than expressed shopping preferences.…”
Section: Discussionmentioning
confidence: 99%
“…En el campo de la salud pública interesaría identificar las estructuras, los mecanismos y los procesos que crean y reproducen el racismo, afectando así la salud de las poblaciones afrodescendientes en Colombia. En otros contextos la literatura muestra que el racismo y la discriminación racial explican ciertos resultados en salud (Paradies, 2006).…”
Section: Discusión Y Conclusionesunclassified